Intestinal barrier function as a key determinant of inflammation and nutritional status in digestive surgery patients: a real-world study - Wang, Jingjing; Yan, Jing; Shi, Linlin; Wang, Ying; Tian, Xiaoxiao; Qi, Yumei; Li, Guoxun (Frontiers in Nutrition, 2025)
IntroductionExisting studies have demonstrated a significant correlation between intestinal barrier and disease outcomes. The intestinal barrier is particularly susceptible to impairment following digestive surgery. The study aimed to elucidate the effects of intestinal barrier impairment on inflammation and nutritional status, as well as the necessity of nutritional treatment for postoperative patients.MethodsWe assessed intestinal barrier integrity by measuring serum biomarkers, diamine oxidase (DAO), D-lactate (D-lac) and lipopolysaccharide (LPS) in 745 consecutive hospitalized patients after digestive surgery and 394 non-surgical patients. Serum levels above established cutoffs (DAO > 10 U/L, D-lac >15 mg/L, LPS > 20 U/L) were defined as positive, corresponding to mucosal injury, increased intestinal permeability, and bacterial translocation. Correlation analyses were performed between intestinal barrier integrity, inflammation, cytokines, and nutritional status. The areas under the receiver operating characteristic (ROC) curves were used to predict severe intestinal barrier impairment. Additionally, changes in intestinal barrier biomarkers were compared after 1 week of nutritional therapy.ResultsPostoperative patients exhibited a high incidence of intestinal barrier impairment. Among the biomarkers, DAO showed the highest positivity rate, followed by D-lac, while LPS was the least frequently elevated. The highest levels of serum DAO, D-lac and LPS were observed in patients with severe intestinal barrier impairment (positive for all three biomarkers). Patients with intestinal barrier impairment exhibited progressively worsening nutritional status and escalating systemic inflammation. The area under the ROC curve for predicting severe intestinal barrier impairment was 0.71. One-week nutritional intervention was significantly associated with improved intestinal barrier function, primarily evidenced by a reduction in intestinal permeability. Early enteral nutrition (EEN) was associated with lower serum DAO, D-lac, and LPS levels. However, patients with aggravated intestinal barrier function after nutritional therapy displayed higher inflammatory markers and failed to achieve improvement in nutritional status compared to those with improved barrier function.ConclusionIntestinal barrier impairment is prevalent in patients undergoing digestive surgery and acts as a key driver of both inflammation and malnutrition. EEN was associated with improvement in intestinal barrier dysfunction. However, delayed or inadequate correction of intestinal barrier impairment may compromise therapeutic outcomes.